Prognose da produção de Eucalyptus camaldulensis dehnh. pela aplicação da função de distribuição sb de Johnson - Silva, Versides Sebastião de Moraes e (2009)
This study was carried out to accomplish the yield projection of Eucalyptus camaldulensis Delnh. in Cuiabá-MT. For the diameter distribution, the Johnson SB’s function was adjusted by the methods of the moments. The model used to express the attributes of the forest was evaluated by the regression analysis. In general, the tests carried out showed that the model presented satisfactory fitting and was unbiased in the graphic analyses of the residues. The efficiency of the prognosis was appraised by the t-test, prognosis deviation and correlation between the predicted and the observed volume at the same age. The modeling process used allowed us to obtain the detailed tendencies of growth. From these tendencies, it can be concluded that the adopted methodology allowed us to obtain the estimates of the current or future production, making use of the group of bio-mathematical models discriminated for each phase of this study.